Are sex and educational level independent predictors of dementia and Alzheimer's disease? Incidence data from the PAQUID project. Issue 2 (1st February 1999) - Letenneur, L; Gilleron, V; Commenges, D; Helmer, C; Orgogozo, J M; Dartigues, J F
Abstract : OBJECTIVES: To examine the age specific risk of Alzheimer's disease according to sex, and to explore the role of education in a cohort of elderly community residents aged 65 years and older. METHODS: A community based cohort of elderly people was studied longitudinally for 5 years for the development of dementia. Dementia diagnoses were made according to the DSM III R criteria and Alzheimer's disease was assessed using the NINCDS-ADRDA criteria. Among the 3675 non-demented subjects initially included in the cohort, 2881 participated in the follow up. Hazard ratios of dementia were estimated using a Cox model with delayed entry in which the time scale is the age of the subjects. RESULTS: During the 5 year follow up, 190 incident cases of dementia, including 140 cases of Alzheimer's disease were identified. The incidence rates of Alzheimer's disease were 0.8/100 person-years in men and 1.4/100 person-years in women. However, the incidence was higher in men than in women before the age of 80 and higher in women than in men after this age. A significant interaction between sex and age was found. The hazard ratio of Alzheimer's disease in women compared with men was estimated to be 0.8 at 75 years and 1.7 at 85 years. The risks of dementia and Alzheimer's disease were associated with a lower educational attainment (hazard ratio=1.8, p<0.001). The increased risk of Alzheimer's disease in women was not changed after adjustment for education. CONCLUSION: Women have a higher risk of developing dementia after the age of 80 than men. Low educational attainment is associated with a higher risk of Alzheimer's disease. However, the increased risk in women is not explained by a lower educational level.